TANGGUNGJAWAB BANK DALAM PENGGUNAAN COMMERCIAL PAPER SEBAGAI SUMBER PENDANAAN PERUSAHAAN - Wahyuningdyah, Kingkin (FIAT JUSTISIA)
Commercial Paper (CP) is one of the types of securities that can be used as a source of corporate financing, in addition Other financing sources. CP issuance process and trade refers to the Decision of the Board of Directors of Bank Indonesia Number 28/32 / KEP / DIR and Bank Indonesia Circular Letter No.28 / 49 / UPG Parties involved in the issuance of CP include banks, both as a regulator of publishing, publishing agents and agents pembayan provisions of this circular letter was not in line with the provisions of Commercial code about the same thing, which considers all the signatures contained in securities is a debtor, and therefore partly responsible for the payment of the securities in question.Â Keywords: Commercial Paper, Bank Responsibility, Corporate Funding word